Contrastive Study of the Semantics of White and Black in Spanish and Chinese Phrases - Yuecheng, Wang; Xiaowe, Zhang (Sinología hispánica. China Studies Review, 2024)
The present work establishes a corpus that includes the phraseological units comprising “white” and “black” in 8 Spanish dictionaries and 6 Chinese dictionaries, within which a quantitative and qualitative analysis is carried out on the semantics of said phraseological units. The study discovers that through the metaphorical and metonymic process, similar figurative meanings come mainly from the physical perception of the environment and one's own colors, and the different meanings are motivated by cultural specificity, especially religions, superstitions, mythologies and legends; in Spanish, the figurative meanings of white and black constitute a violent contrast, while this antagonism is blurred in Chinese. Furthermore, in both languages, black is mainly associated with negativity, but the connotation of white is mixed and complicated; in the corpus, white in Chinese belongs to broader grammatical classes, which not only serves as a noun or adjective, but also a verb and adverb; and the verbalized white in Chinese is usually associated with “speak” and the adverbialized one is linked to the meanings “in vain” or “without cost.”